Concise encyclopedia of preaching - Willimon, William H.; Lischer, Richard (Louisville Westminster/John Knox, 1995)
Donated by the Australian College of Theology, 1996
Keywords: Preaching -- encyclopaedias; Clergy -- biography -- dictionaries